INFLUENCE OF ENTREPRENEURIAL JOURNALISM ON FREELANCE JOURNALISTS IN THE SHRINKING MEDIA INDUSTRY IN SOUTH-WEST, NIGERIA - John James, Adebayo; Benjamin Kayode, Ogundeji; Olalekan Rufai, Mustapha; Olawunmi, Bisi (African Journal of Social and Behavioural Sciences, 2024)
Entrepreneurial journalism is gaining popularity in Nigeria's entrepreneurial and media discourses. The worsening unemployment issues in Nigeria have made freelance journalists devise creative means to survive the onslaught of job crises. Thus, this study is designed to investigate the influence of entrepreneurial journalism on freelance journalists in South-Western Nigeria. The study adopted a mixed method. The survey method and paired depth interview were used to investigate the influence of entrepreneurial journalism on freelance journalistic practice, techniques of entrepreneurial journalism, and barriers to entrepreneurial journalism among freelance journalists. Findings showed that economic factors have compelled most freelance journalists to embrace entrepreneurial journalistic practices. Findings also showed that blogging, YouTube videos, and other audio and video content on social media are the techniques of entrepreneurial journalism in South-Western Nigeria. Findings showed that lack of objectivity and fairness in news reportage, as well as monetary consideration over balanced news reportage, has been a barrier to entrepreneurial journalistic practices in South-Western Nigeria. Therefore, it is recommended that entrepreneurial journalists not only consider the ethics of journalism in their daily journalistic activities but also be mindful of the unwholesome influence of excessive attention to economic considerations in their journalistic practices. Entrepreneurial values of all digital and social media-based platforms must be taught to students of mass communication and journalism to make them self-employed and self-reliant when they eventually graduate from school. A regulatory agency, like the National Broadcast Commission, that regulates the affairs and activities of all broadcasting stations in Nigeria, must be established to regulate the activities of entrepreneurial journalists who have their independent radio or television on the internet so that the issues of lack of objectivity, fairness and unbalanced news reportage could be addressed.